Oropharyngeal dysphagia in preschool children with cerebral palsy: Oral phase impairments - Benfer, K.; Weir, K.; Bell, K.; Ware, R.; Davies, P.; Boyd, Roslyn (2014)
© 2014 Elsevier Ltd. Purpose: This study aimed to document the prevalence and patterns of oral phase oropharyngeal dysphagia (OPD) in preschool children with cerebral palsy (CP), and its association with mealtime duration, frequency and efficiency. Methods: Cross-sectional population-based cohort study of 130 children diagnosed with CP at 18-36 months ca (mean. =. 27.4 months, 81 males) and 40 children with typical development (mean. =. 26.2, 18 males). Functional abilities of children with CP were representative of a population sample (GMFCS I. =. 57, II. =. 15, III. =. 23, IV. =. 12, V. =. 23). Oral phase impairment was rated from video using the Dyspahgia Disorders Survey, Schedule for Oral Motor Impairment, and Pre-Speech Assessment Scale. Parent-report was collected on a feeding questionnaire. Mealtime frequency, duration and efficiency were calculated from a three day weighed food record completed by parents. Gross motor function was classified using the Gross Motor Function Classification System (GMFCS). Results: Overall, 93.8% of children had directly assessed oral phase impairments during eating or drinking, or in controlling saliva (78.5% with modified cut-points). Directly assessed oral phase impairments were associated with declining gross motor function, with children from GMFCS I having a 2-fold increased likelihood of oral phase impairment compared to the children with TD (OR. =. 2.0, p=. 0.18), and all children from GMFCS II-V having oral phase impairments. Difficulty biting (70%), cleaning behaviours (70%) and chewing (65%) were the most common impairments on solids, and difficulty sipping from a cup (60%) for fluids. OPD severity and GMFCS were not related to mealtime frequency, duration or efficiency, although children on partial tube feeds had significantly reduced mealtime efficiency. Conclusions: Oral phase impairments were common in preschool children with CP, with severity increasing stepwise with declining gross motor function. The prevalence and severity of oral phase impairments were significantly greater for most tasks when compared to children with typical development, even for those with mild CP. Children who were partially tube fed had significantly lower feeding efficiency, so this could be a useful early indicator of children needing supplementation to their nutrition (through increasing energy density of foods/fluids, or tube feeds).